PEGylated chitosan / doxorubicin nanoparticles and conjugated with monoclonal antibodies for breast cancer therapy - Zidan, Omar Helmi (AUC Knowledge Fountain, 2020)
The potential of nanobiomedical field for developing a promising therapeutic nano-sized drug delivery system is seen to be a great pharmaceutical trend for encapsulation and release of various antineoplastic drugs. In this context, the current work is targeting preparation of biodegradable chitosan nanoparticles (CSNP) that have been intended for selective and sustained release of doxorubicin (DOX) within breast tumor microenvironment. Surface modification of these CSNP with Polyethylene glycol (PEG) was performed in order for enhancing its blood circulation time without being opsonized or captured by immunogenic reticuloendothelial system (RES). PEG has maintained high particles stability profile and enhanced its surface positive charge for the sake of intracellular attachment via electrostatic attachment with negatively charged tumor cell membrane. Advanced tumor selectivity has been achieved through functionalization of two different types of breast cancer specific monoclonal antibodies (mAb); anti-human mammaglobin (Anti-hMAM) and anti-human epidermal growth factor (Anti-HER2) in two different separate nano formulations. This functionalization has the potential of evading systemic side effects of parenteral free DOX and promoting cancerous endocytosis through receptor mediated interaction. In-vitro cytotoxicity effects of PEGylated DOX loaded CSNP, free DOX, Anti-HER2 PEGylated DOX loaded CSNP and Anti-hMAM PEGylated DOX loaded CSNP were tested against breast cancer cell line (MCF7) and normal fibroblast cell line (L929). Notably, Anti-hMAM PEGylated DOX loaded CSNP and Anti-HER2 PEGylated DOX loaded CSNP formulations were the most cytotoxic against MCF7 cancer cells than L929 normal cells compared to free DOX. Confirmatory bright filed images of the two cell lines have exhibited cancerous cellular damage after 24 hours exposure time to these nano formulations. Finally, we believe that dose dependent system toxicity of freely ingested DOX can be hindered with such targeted nano formulated drug delivery system.